2020
DOI: 10.1177/0363546520916435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patella Alta on the Native Anatomometricity of the Medial Patellofemoral Complex: A Cadaveric Study

Abstract: Background: Patella alta has been identified as an important risk factor for lateral patellar instability and medial patellofemoral complex (MPFC) reconstruction failure. Purpose: To evaluate the length changes of the MPFC at multiple possible reconstruction locations along the extensor mechanism in varying degrees of patella alta throughout knee motion. Study Design: Controlled laboratory study. Methods: Eight fresh-frozen cadaveric knees were used in this study. The MPFC was identified and dissected with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…From 10 original articles included in this review, nine studies identified multiple fibers of MPFL for assessment of length change [7,14,21,22,[24][25][26][27][28] and one study assessed only a single fiber [23]. Various femoral and patellar attachments were analyzed, as specified in Table 2.…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…From 10 original articles included in this review, nine studies identified multiple fibers of MPFL for assessment of length change [7,14,21,22,[24][25][26][27][28] and one study assessed only a single fiber [23]. Various femoral and patellar attachments were analyzed, as specified in Table 2.…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
“…Nine studies performed measurements in 3D [14,[21][22][23][24][25][26][27][28]; however, only in four was MPFL measured with respect to its convexity [7,14,24,25]. CT was utilized in four studies [14,22,24,25], caliper in two studies [21,27], MRI in one study [7], suture in one study [23], and other measurement methods in two studies [26,28]. Only five out of 10 studies reported precision of measurements [14,21,23,24,27].…”
Section: Study Design As the Source Of Heterogeneity 41 Identification Of Measured Fibers And Measurement Methodsmentioning
confidence: 99%
See 3 more Smart Citations